2013
DOI: 10.1680/geot.13.p.041
|View full text |Cite
|
Sign up to set email alerts
|

Hydromechanical behaviour of a volcanic ash

Abstract: This paper presents experimental analysis and numerical modelling aimed at improved understanding and prediction of the hydromechanical behaviour of volcanic ash at various states of saturation. Results from a comprehensive experimental programme are presented in order to characterise the response of the material in terms of matric suction and confining stress changes. The evolution of the yield stress at different suction levels has been quantified. The volumetric response with suction variations allowed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 20 publications
1
8
0
4
Order By: Relevance
“…Most of the fully coupled unsaturated numerical formulations that are based on the traditional FE method can only model the initial failure surface, and this would not be a good estimate when predicting landslide volume as it can be much larger during the post‐failure motion. Because of the high level of risk associated with landslides in steep terrains, these simulations use some of the most common features such as slope angle that lies between 35°and 45°, internal friction angle that lies between 35°and 39°, existing shallow soil covers above the bedrock that can result in a perched water table and very low‐lying regional water table . As mentioned earlier, this case study was inspired by the full‐scale field test performed in Rüdlingen, Switzerland , where a landslide of 130 m 3 volume was observed after 15 h of rainfall.…”
Section: Validation and Application Examplesmentioning
confidence: 99%
“…Most of the fully coupled unsaturated numerical formulations that are based on the traditional FE method can only model the initial failure surface, and this would not be a good estimate when predicting landslide volume as it can be much larger during the post‐failure motion. Because of the high level of risk associated with landslides in steep terrains, these simulations use some of the most common features such as slope angle that lies between 35°and 45°, internal friction angle that lies between 35°and 39°, existing shallow soil covers above the bedrock that can result in a perched water table and very low‐lying regional water table . As mentioned earlier, this case study was inspired by the full‐scale field test performed in Rüdlingen, Switzerland , where a landslide of 130 m 3 volume was observed after 15 h of rainfall.…”
Section: Validation and Application Examplesmentioning
confidence: 99%
“…On the other hand, for soils that contain a "shielding skeleton" of coarse particles it is possible to envisage that the shielding skeleton limits the shrinkage on drying of the bulk sample while the clayey fraction may continue to shrink and create macropores (Romero, 2013). It is well known that collapse can occur in silty soils, similar to the loess described by Muñoz-Castelblanco et al (2011) and the volcanic ash described by Ferrari et al (2013). This paper on the other hand is concerned with a high plasticity clay.…”
Section: Introductionmentioning
confidence: 98%
“…namely ashy soil 'A' in previous experiments (Bilotta et al, 2005), which is generally found at the bedrock contact of shallow pyroclastic deposits. It is very loose soil (n = 0•645-0•651) with a metastable structure along steep slopes (Sorbino et al, 2011), similar to other volcanic soils (Ferrari et al, 2013). The grain size distribution consists in 43•6-51•9% sand, 43•9-54•03% silt and 1•4-4•7% clay.…”
Section: Investigated Soilmentioning
confidence: 79%